La creación de una radio comunitaria y su incidencia en el desarrollo cultural de la parroquia de Zumbahua, del cantón Pujilí, provincia Cotopaxi - Toaquiza Toaquiza, Washington Medardo (2015)
At present, due to the growing demand for information, different communities have felt the need to have their own radio station to give notices, to know social and cultural aspects better; and, to reach the whole population to keep them it informed. Considering these important aspects, it appears opportune to work on a proyect for creating a community radio that will contribute to the cultural development of Zumbahua parish wich belongs to the Pujili Cantón….